2016
DOI: 10.1002/hrdq.21256
|View full text |Cite
|
Sign up to set email alerts
|

Never Too Early: Learning Transfer System Factors Affecting Motivation to Transfer Before and After Training Programs

Abstract: The influence of various learning transfer system factors on transfer motivation has been demonstrated in previous research. However, studies examining the influences of different factors simultaneously and at different points in time (i.e., before and after training programs) are missing. We seek to fill this gap by collecting data at two points of measurement to find out which Learning Transfer System Inventory ( LTSI ) factors influence IntroductionDeveloping employees' knowledge and skills through training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0
16

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 76 publications
9
86
0
16
Order By: Relevance
“…Generally, peer support and feedback/coaching seem to have a powerful motivating function in exerting agency concerning transfer of training (Bates & Holton, ; Damsa et al ., ; Kauffeld et al ., ; Massenberg et al ., ; Tian et al ., ; Van den Bossche et al ., ). Does this imply that supervisors are less important?…”
Section: Discussionmentioning
confidence: 99%
“…Generally, peer support and feedback/coaching seem to have a powerful motivating function in exerting agency concerning transfer of training (Bates & Holton, ; Damsa et al ., ; Kauffeld et al ., ; Massenberg et al ., ; Tian et al ., ; Van den Bossche et al ., ). Does this imply that supervisors are less important?…”
Section: Discussionmentioning
confidence: 99%
“…Further, investigating the transfer of learning to the job might offer a potential avenue for unpacking how leaders might influence their followers following leadership training. Massenberg, Schulte and Kauffeld (2017) found that pre-training motivation to learn and self-efficacy beliefs were particularly important for transferring training to the workplace. A recent review of employee soft skills training, which are intra-and inter-personal skills such as managing oneself and one's interactions with others, found that autonomy, colleague and supervisor support, workload, and the organisational learning climate were particularly influential in enabling the transfer of learning to the job (Botke, Jansen, Khapova & Tims, 2018).…”
Section: Directions For Future Researchmentioning
confidence: 97%
“…As noted in our introduction, since our 1988 review, many empirical studies have been conducted examining the relationship between predictor constructs and transfer outcomes (see, e.g., Massenberg, Schulte, & Kauffeld, ). Blume et al () conducted a meta‐analysis of this empirical research and showed that certain individual difference factors such as conscientiousness and certain contextual factors such as supervisory support predict transfer outcomes such as use and effectiveness.…”
Section: Study Ways To Optimize Impact On Transfermentioning
confidence: 99%